Inflammatory Dendritic Cells, Regulated by IL-4 Receptor Alpha Signaling, Control Replication, and Dissemination of Leishmania major in Mice - Hurdayal, Ramona; Nieuwenhuizen, Natalie Eva; Khutlang, Rethabile; Brombacher, Frank (Frontiers in Cellular and Infection Microbiology, 2020)
Leishmaniasis is a vector-borne disease caused by Leishmania parasites. Macrophages are considered the primary parasite host cell, but dendritic cells (DCs) play a critical role in initiating adaptive immunity and also controlling Leishmania infection. Accordingly, our previous study in CD11ccreIL-4R-/lox mice, which have impaired IL-4 receptor alpha (IL-4R) expression on CD11c+ cells including DCs, confirmed a protective role for IL-4/IL-13-responsive DCs in replication and dissemination of parasites during cutaneous leishmaniasis. However, it was unclear which DC subset/s was executing this function. To investigate this, we infected CD11ccreIL-4R-/lox and control mice with L. major GFP+ parasites and identified subsets of infected DCs by flow cytometry. Three days after infection, CD11b+ DCs and CD103+ DCs were the main infected DC subsets in the footpad and draining lymph node, respectively and by four weeks post infection, Ly6C+ and Ly6C- CD11b+ DCs were the main infected DC populations in both the lymph nodes and footpads. Interestingly, Ly6C+CD11b+ inflammatory monocyte-derived DCs but not Ly6C-CD11b+ DCs hosted parasites in the spleen. Importantly, intracellular parasitism was significantly higher in IL-4Rα deficient DCs. In terms of DC effector function, we found no change in the expression of pattern-recognition receptors (TLR4 and TLR9) nor in expression of the co-stimulatory marker, CD80, but MHCII expression was lower in CD11ccreIL-4R-/lox mice at later time-points compared to the controls. Interestingly, in CD11ccreIL-4R-/lox mice, which have reduced Th1 responses, CD11b+ DCs had impaired iNOS production, suggesting that DC IL-4Rexpression and NO production is important for controlling parasite numbers and preventing dissemination. Expression of the alternative activation marker arginase was unchanged in CD11b+ DCs in CD11creIL-4R-/lox mice compared to littermate controls, but RELM- was upregulated, suggesting IL-4R-independent alternative activation. In summary, L. major parasites may use Ly6C+CD11b+ inflammatory DCs derived from monocytes recruited to infection as “Trojan horses” to migrate to secondary lymphoid organs and peripheral sites, and DC IL-4R expression is important for controlling infection.